Interpersonal Functioning in Obsessive-Compulsive Personality Disorder - Cain, Nicole M. (J Pers Assess, 2014)
The core symptoms of obsessive-compulsive personality disorder (OCPD) often lead to interpersonal difficulties. However, little research has explored interpersonal functioning in OCPD. The current study examined interpersonal problems, interpersonal sensitivities, empathy, and systemizing, the drive to analyze and derive underlying rules for systems, in a sample of 25 OCPD individuals, 25 individuals with comorbid OCPD and obsessive-compulsive disorder (OCD), and 25 healthy controls. We found that OCPD individuals reported hostile-dominant interpersonal problems and sensitivities with warm-dominant behavior by others while OCPD+OCD individuals reported submissive interpersonal problems and sensitivities with warm-submissive behavior by others. Individuals with OCPD, with and without OCD, reported less empathic perspective taking relative to healthy controls. Finally, we found that OCPD males reported a higher drive to analyze and derive rules for systems than OCPD females. Overall, results suggest that there are interpersonal deficits associated with OCPD and the clinical implications of these deficits are discussed.